Reverse Digital Artery Island Flap for Finger-Tip Defects - S Raja Sabapathy; S Suresh Babu; Anil K Agarwal (Indian Journal of Plastic Surgery)
Five finger-tip amputations and two fingers with pulp-loss were covered with reverse digital artery island flaps from the same finger. The flap was successful in all cases and provided cosmetically and functionally acceptable results. One patient had venous congestion, but the flap survived. This flap would be particularly useful when the nature of injury precludes the use of local advancement flaps and cross-finger flaps.